1991
DOI: 10.2307/1591309
|View full text |Cite
|
Sign up to set email alerts
|

Type A Influenza Viruses in Waterfowl in Ohio and Implications for Domestic Turkeys

Abstract: Because ducks are considered an important reservoir for type A influenza virus, and type A influenza viruses had not been recovered from ducks in Ohio, a 3-year virus surveillance study was conducted in Ohio waterfowl and waterfowl passing through Ohio to determine if domestic turkeys were at risk of exposure to avian influenza (AI) viruses from the waterfowl reservoir. The prevalence of AI infections in ducks during the fall migration averaged about 5.9%. The 55 waterfowl-origin type A influenza viruses recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The low prevalence or failure to detect AIV in these birds at sites other than the Dela- ware Bay is consistent with other studies (Slepuskin et al, 1972;Zakstelskaya et al, 1974;Bahl et al, 1977;Boudreault et al, 1980;Thorsen et al, 1980;Honda et al, 1981;Tsubokura et al, 1981;Abenes et al, 1982;Sinnecker et al, 1983;Mackenzie et al, 1984;Nettles et al, 1985;Slemons et al, 1991;Astorga et al, 1994;Okazaki et al, 2000;Munster et al, 2007). Although the reasons for this spatiotemporal cluster are not clear, one possibility is the high concentration of shorebirds that use this site during May.…”
Section: Discussionsupporting
confidence: 87%
“…The low prevalence or failure to detect AIV in these birds at sites other than the Dela- ware Bay is consistent with other studies (Slepuskin et al, 1972;Zakstelskaya et al, 1974;Bahl et al, 1977;Boudreault et al, 1980;Thorsen et al, 1980;Honda et al, 1981;Tsubokura et al, 1981;Abenes et al, 1982;Sinnecker et al, 1983;Mackenzie et al, 1984;Nettles et al, 1985;Slemons et al, 1991;Astorga et al, 1994;Okazaki et al, 2000;Munster et al, 2007). Although the reasons for this spatiotemporal cluster are not clear, one possibility is the high concentration of shorebirds that use this site during May.…”
Section: Discussionsupporting
confidence: 87%
“…The N1 subtype has been identified from wild birds relatively frequently, although the N2, N6, and N8 subtypes have been reported to be more common (9). Since the HA and NA subtypes are independent of each other, few viruses with the H5N1 combination have previously been isolated from wild birds in North America (19). Upon sequencing, several isolates which had been reported to be H5N1 (17) or either H5 or N1 based on serology (unpublished data), had to be excluded, as they turned out to be different HA or NA subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported negative results for IAV detection in wood ducks, but most of these studies included fewer than 60 individuals (Rosenberger et al, 1974;Bahl et al, 1975;Webster et al, 1976;Kocan et al, 1979;Nettles et al, 1985;Hinshaw et al, 1986;Slemons et al, 1991). Three studies have attempted to isolate virus from more than 100 wood ducks, and two of these studies reported a low prevalence (less than 2.5%) of viral shedding compared to other dabbling duck species Goekjian et al, 2011;Wilcox et al, 2011).…”
Section: Introductionmentioning
confidence: 99%